Tubercular epidural abscess presenting with acute lower back pain: A rare case report - Lavindra Tomar; Gaurav Govil; Pawan Dhawan (Journal of Orthopaedic Reports, 2022)
Abstract:: Introduction: Acute low back pain (LBP) in a young adult have common aetiology of mechanical, postural, trauma, or infection related causes. An isolated acute onset LBP may occasionally present diagnostic challenges. An associated weakness in lower limbs may have grave clinical implications. Any progressive neurological deficit of acute nature may warrant an emergency surgical measure. The thorough history taking, astute clinical examination, and diagnostic imaging should guide regarding the possible pathology and its management. A lumbar spinal epidural abscess (SEA) has been rarely reported as a cause for acute LBP without fever and neurological deficit due to Mycobacterium tuberculosis (MBT) aetiology. Chronic presentations are commonly reported in elderly age groups. Case report: We present a case of SEA presenting with only acute LBA in a young adult male without any other associated symptoms and showing progression to an impending cauda equina which required an emergency surgical laminectomy, decompression and abscess evacuation for the management. Discussion: The case report highlights the significance of an astute clinical assessment for an acute LBP presentation in an emergency department (ED). Any undiagnosed or late diagnosed presentation may have serious consequences and clinical implications for the emergency physician and the orthopaedic clinician. A prompt diagnosis and keen observation in the ED may avoid unfavourable outcomes. Conclusion: There is a need for clinicians and emergency physicians to consider SEA in the differential diagnosis for acute LBA even without neurological deficit, to avoid a life-threatening emergency.